Emotion Regulation as the Key to Coping with Work Stress in Working Students - Sri Hartini; Cornelissen F; Cheerly Xiesoria; Angeli Kitaroe; Megawati Ginting; Rina Mirza; Lodiana Ayu (Psikostudia : Jurnal Psikologi, 2025)
Working students faced academic and work-related pressures that could trigger job stress, affecting psychological well-being and performance. Emotion regulation played a crucial role in helping individuals adaptively cope with pressure. This study analyzed the relationship between emotion regulation and job stress among 94 working students using a quantitative method with a correlational analysis technique. Data were collected through a questionnaire using the Job Stress Scale based on Robbins et al. (2019) and the Emotion Regulation Scale from Gross (2015). The results showed a significant negative relationship between emotion regulation and job stress, where students with good emotion regulation experienced lower job stress levels. The psychological aspect of job stress had the strongest correlation with emotion regulation compared to physiological and behavioral aspects. Individuals who used adaptive emotion regulation strategies were better at managing pressure than those who used maladaptive strategies. These findings supported Gross’s theory and previous research on job stress and psychological well-being. The study’s implications emphasized the importance of emotion regulation-based interventions in academic and work environments to help students manage stress effectively and maintain a balance between academic and job demands. Mahasiswa yang bekerja menghadapi tekanan akademik dan pekerjaan yang dapat memicu stres kerja, berdampak pada kesejahteraan psikologis dan kinerja. Regulasi emosi berperan penting dalam membantu individu mengatasi tekanan secara adaptif. Penelitian ini menganalisis hubungan antara regulasi emosi dan stres kerja pada 94 mahasiswa yang bekerja, menggunakan metode kuantitatif dengan teknik analisis korelasional. Data dikumpulkan melalui kuesioner skala Stres Kerja berdasarkan teori Robbins et al. (2019) dan skala Regulasi Emosi dari Gross (2015). Hasil penelitian menunjukkan hubungan negatif signifikan antara regulasi emosi dan stres kerja, di mana mahasiswa dengan regulasi emosi yang baik mengalami tingkat stres kerja lebih rendah. Aspek psikologis stres kerja memiliki korelasi paling kuat dengan regulasi emosi dibandingkan aspek fisiologis dan perilaku. Individu yang menggunakan strategi regulasi emosi adaptif lebih mampu mengelola tekanan dibandingkan yang menggunakan strategi maladaptif. Temuan ini mendukung teori Gross serta penelitian sebelumnya mengenai stres kerja dan kesejahteraan psikologis. Implikasi penelitian ini menekankan pentingnya intervensi berbasis regulasi emosi dalam lingkungan akademik dan pekerjaan untuk membantu mahasiswa mengelola stres secara efektif, serta menjaga keseimbangan antara tuntutan akademik dan pekerjaan.